WHAT IS MALARIA? - Tantular, Indah Setyawati (Institute of Topical Disease Universitas Airlangga, 2010)
Malaria persists as an undiminished global problem and still is the cause of much human morbidity and mortality. Although the disease has been eradicated in many temperate zones, it continues to be endemic throughout much of the tropics and subtropics. Many tools for understanding its biology and epidemiology are well developed, with a particular richness of comparative genome sequences. Studies of the epidemiology, prevention, and treatment of human malaria methods, and analyses of parasite polymorphisms have long had have already been influenced by the availability of molecular useful and highly informative applications. The molecular epidemiology of malaria is currently undergoing its most substantial revolution as a result of the genomic information and technologiesthat are available in well-resourced centers. However, great progress in malaria control has been made in some highly endemic countries. Vector control is assuming a new importance with the significant reductions in malaria burden achieved using combined malaria control interventions. Education of health workers and communities about malaria prevention, diagnosis and treatment is a vital component of effective case management, especially as diagnostic policies change.